The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1016/0092-8674(95)90417-4
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell progenitor is transformed by a conditional v-Rel estrogen receptor fusion protein v-ReIER

Abstract: A conditional v-Rel estrogen receptor fusion protein, v-RelER, causes estrogen-dependent but otherwise unaltered v-rel-specific transformation of chicken bone marrow cells. Here, we demonstrate that such v-relER-transformed cells exhibit B lymphoid determinants in line with earlier studies on v-rel-transformed cells. However, following inactivation of v-RelER oncoprotein activity by administration of an estrogen antagonist, cells differentiate into antigen-presenting dendritic cells as judged by several morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Moreover, vRel-transformed cell lines, established by in vitro infection of chicken spleen cells and which do not shed helper virus, can induce fatal tumors with as few as 100 cells when injected into histocompatible chickens (Lewis et al, 1981). Cells transformed in vitro by v-Rel have been reported to have characteristics of immature pre-B/pre-T cells (Beug et al, 1981;Chen et al, 1988;Morrison et al, 1991;Zhang et al, 1989), abnormal B cells (Chen et al, 1988), immature and mature B cells (Benatar et al, 1991(Benatar et al, , 1992Boehmelt et al, 1995;Keller et al, 1979;Lewis et al, 1981;Sasaki and Koyama, 1989;Shibuya et al, 1982;Zhang et al, 1991), T cells (Barth et al, 1990;Marmor et al, 1993;Schat et al, 1992), myeloid cells (Barth et al, 1990;Morrison et al, 1991), erythroid cells (Morrison et al, 1991), and pre-dendritic cells (Boehmelt et al, 1995).…”
Section: V-rel As a Member Of The Rel/nf-kb Family Of Transcription Fmentioning
confidence: 99%
“…Moreover, vRel-transformed cell lines, established by in vitro infection of chicken spleen cells and which do not shed helper virus, can induce fatal tumors with as few as 100 cells when injected into histocompatible chickens (Lewis et al, 1981). Cells transformed in vitro by v-Rel have been reported to have characteristics of immature pre-B/pre-T cells (Beug et al, 1981;Chen et al, 1988;Morrison et al, 1991;Zhang et al, 1989), abnormal B cells (Chen et al, 1988), immature and mature B cells (Benatar et al, 1991(Benatar et al, , 1992Boehmelt et al, 1995;Keller et al, 1979;Lewis et al, 1981;Sasaki and Koyama, 1989;Shibuya et al, 1982;Zhang et al, 1991), T cells (Barth et al, 1990;Marmor et al, 1993;Schat et al, 1992), myeloid cells (Barth et al, 1990;Morrison et al, 1991), erythroid cells (Morrison et al, 1991), and pre-dendritic cells (Boehmelt et al, 1995).…”
Section: V-rel As a Member Of The Rel/nf-kb Family Of Transcription Fmentioning
confidence: 99%
“…c-Myb, a sequence-speci®c DNA-binding protein, is thought to regulate genes whose expression is incompatible with cellular di erentiation as re¯ected in its expression pattern and biological properties (Graf, 1992). Surprisingly, we found that c-myb mRNA increased upon estrogen withdrawal, conditions under which v-RelER cells begin to di erentiate into dendritic and neutrophilic cells (Boehmelt et al, 1995).…”
Section: Expression Of DI Erentially Regulated Genes In V-reler Cellsmentioning
confidence: 59%
“…Despite this considerable heterogeneity, several authors have shown that monocytes/macrophages and dendritic cells derive from a common pluripotential haematopoietic progenitor cell in the bone marrow [6,7,[9][10][11][12]. Under appropriate conditions, monocytes/macrophages and dendritic cells can also develop from CD34 + blood stem cells [13,14].…”
Section: A Question Of Paternitymentioning
confidence: 99%